The Birth and Formation of the Nigerian Army: A Background to the Conundrum of Ethnic Rivalry and Military Doctrine - William Abiodun Duyile (Britain International for Academic Research (BIAR-Publisher), 2023)
This study examined the genesis of the Nigerian Army, the activities in context with policy and platform preference in tactics, strategy and doctrine. Nigeria’s response to the myriad of challenges faced by the Nigerian Army and the role it played pre- 1970. The research also traced the history of the Nigeria Army, and postulates factors in the organization that engendered ethnic rivalry. A retrospect and review of the facts was made, in order that scholars would have an insight on perceptions as well as the reasons why the choice of strategic platform favored the Army. The research identified the reasons why the Army is considered the number one force in the Nigerian state and the land platform is most favored. The other contribution to knowledge is the correlation between ethnic rivalry and the choice of platform.